IMPLEMENTASI PENGUATAN PENDIDIKAN KARAKTER MELALUI KEGIATAN TAHFIDZ AL - QUR’AN DALAM MENINGKATKAN MUTU PESANTREN ( STUDI ANALISIS DI PONPES AL-IMAM ASY SYAFI’I DUMAI ) - Dirgham,; Erjati Abas,; Risqun Iqbal,; Rina Setyaningsih, (UNISAN JURNAL, 2023)
The need for urgent character education to be carried out is the presence of symptoms that signal the erosion of the nation's character, in the era of globalization. Freedom of will, without standard rules, climate of freedom, is not infrequently interpreted as freedom of action, The purpose of this paper is to discuss how the implementation model of strengthening character education in Islamic boarding schools through the teaching and learning process of tahfidz Al-Qur'an, for the Qur'an is a holy book that is kept in order, which leads to a straight path. This research uses qualitative research, supported by data collection tools used in this study are observation, interviews and documentation, supported by Primary data and skunder at Pondok Pesantren Al - Imam Asy Syafi'I Dumai, The reason why the author uses qualitative research is because qualitative research is not just about producing data or information that is difficult to find through quantitative methods, but also must produce meaningful information. Based on the analysis of the data used, it can be concluded that the cultivation of character education through the tahfidz Al-Qur'an program at the Al Imam Asy Islamic Boarding School - Syafi'I implemented thoroughly in the study of the Tahfidz Al-Qur'an program, as exemplified by the prophet Muhammad sallallahu 'alaihi wa sallam. To make this happen, of course, it is recommended to the principal, ustadz and pesantren employees to make themselves suri tauladan in implementing character education.